Diagnostic Values of Electrochemiluminescent Detection of Urinary CYFRA21‐1 and FDP and Their Combined Detection in Bladder Cancer - Zhuoran Li; Lu Xia; Yamin Li; Tao Huang; Ning Yang; Shannai Li; Yinyin Luo; Yaoyao Yang; Jian Zhang; Song Wu; Qifang Lei (Cancer Medicine)
ABSTRACT Background Bladder cancer is the most common malignant tumor in the urinary system. The acquisition of urine samples has the advantages of being rapid and painless, and it can directly contact the lesions. It is an ideal source of non‐invasive tumor markers. The problems with urine markers are low specificity, the propensity for false positives or missed detections, and there is no unified diagnostic standard to measure the test results, which limits the clinical application of urine markers. In this study, we evaluate the diagnostic values of Cytokeratin 19 fragment (CYFRA21‐1), Fibrin/fibrinogen degradation products (FDP) and CYFRA21‐1 + FDP in bladder cancer, with the objective to expand the application scope of urinary tumor markers in the diagnosis of bladder cancer. Methods We evaluated the performances of the CYFRA21‐1 assay kit (electrochemiluminescence) and/or FDP assay kit (electrochemiluminescence) in detecting bladder cancer. CYFRA21‐1 and FDP levels were determined in urine samples from 467 participants in South China Hospital of Shenzhen University and Shenzhen Luohu People's Hospital. We performed performance validation of the CYFRA21‐1 and FDP kits, established normal biological reference intervals, and finally analyzed the data to assess their diagnostic efficacies alone or in combination. Results The bladder cancer group had significantly higher urinary levels of CYFRA21‐1 and FDP than the control group. The areas under the receiver operating characteristic curves (ROC‐AUCs) of CYFRA21‐1, FDP, and CYFRA21‐1 + FDP were 0.929, 0.857, and 0.935, respectively, for discriminating bladder cancer cases from controls. The ROC‐AUC of CYFRA21‐1 and FDP in combination was higher than that of any index alone. Conclusions Both CYFRA21‐1 and FDP have good diagnostic values in predicting bladder cancer. In addition, combined detection of urinary CYFRA21‐1 and FDP by electrochemiluminescence has better differentiation ability compared with each index alone and may be used for early screening and recurrence monitoring in bladder cancer.